Helping Alliance and Unmet Needs in Routine Care of People With Severe Mental Illness Across Europe: A Prospective Longitudinal Multicenter Study. Issue 4 (April 2017) - Arnold, Katrin; Loos, Sabine; Mayer, Benjamin; Clarke, Eleanor; Slade, Mike; Fiorillo, Andrea; Del Vecchio, Valeria; Égerházi, Anikó; Ivánka, Tibor; Munk-Jørgensen, Pøvl; Krogsgaard Bording, Malene; Kawohl, Wolfram; et al.
Abstract : Abstract: The helping alliance (HA) refers to the collaborative bond between patient and therapist, including shared goals and tasks. People with severe mental illness have a complex mixture of clinical and social needs. Using mixed-effects regression, this study examined in 588 people with severe mental illness whether an increase in the HA is associated with fewer unmet needs over time, and whether change in the HA precedes change in unmet needs. It was found that a reduction in unmet needs was slower in patients with higher HA ( B = 0.04, p < 0.0001) only for patient-rated measures. Improvement in both patient-rated and staff-rated HA over time was associated with fewer subsequent patient-rated ( B = −0.10, p < 0.0001) and staff-rated ( B = −0.08, p = 0.0175) unmet needs. With positive changes in the HA preceding fewer unmet needs, findings provide further evidence for a causal relationship between alliance and outcome in the treatment of people with severe mental illness.